Antioxidants, quinone reductase inducers and acetylcholinesterase inhibitors from Spondias tuberosa fruits - Zeraik, Maria Luiza [UNESP]; Queiroz, Emerson Ferreira; Marcourt, Laurence; Ciclet, Olivier; Castro-Gamboa, Ian [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Cuendet, Muriel; da Silva Bolzani, Vanderlan [UNESP]; Wolfender, Jean-Luc (Elsevier, 2016)
The methanolic extract of umbu (Spondias tuberosa) presented high antioxidant activities in the DPPH, ABTS and ORAC assays, as well as acetylcholinesterase (AChE) inhibition activity. The dichloromethane extract exhibited cancer chemopreventive activity, with a quinone reductase induction in Hepa1c1c7 cells. The localization of the active compounds was performed by HPLC activity-based profiling, and preliminary structural information was obtained by HPLC-PAD-ESI-MS and UHPLC-TOF-HRMS. The main constituents from the methanolic extract were efficiently isolated in a single step by preparative MPLC-UV. Two new natural products were identified, together with five known compounds. The structures of the compounds were elucidated by 2D NMR and ESI-HRMS. The dichloromethane extract was fractionated by SPE and by semi-preparative HPLC-UV-ELSD. Using this approach, one anacardic acid derivative was isolated. However, this compound was not responsible for QR induction. This study highlights the potential of umbu as an active ingredient for functional food formulations.
Keywords: Acetylcholinesterase inhibition; Antioxidant activity; Cancer chemopreventive activity; Quinone reductase induction; Spondias tuberosa fruits; UHPLC/TOF/MS